2009
DOI: 10.2174/092986709789178037
|View full text |Cite
|
Sign up to set email alerts
|

Selective Matrix Metalloproteinase Inhibitors for Cancer

Abstract: The matrix metalloproteinases are a family of nearly 30 enzymes that are intimately involved in tissue remodeling. Disease processes associated with the matrix metalloproteinases are generally related to imbalance between the inhibition and activation of matrix metalloproteinases resulting in excessive degradation of the extracellullar matrix. These include osteoarthritis, rheumatoid arthritis, tumor metastasis and congestive heart failure. Despite massive research and development efforts, there are only two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 129 publications
(153 reference statements)
2
42
0
Order By: Relevance
“…MshB is an attractive drug target because it catalyzes the rate-limiting step in MSH biosynthesis (11), it is a metalloenzyme (12)(13)(14), and the three-dimensional structure is known (15,16). There are past successes in targeting metalloenzymes, including inhibitors of carbonic anhydrase, matrix metalloproteases, and angiotensin-converting enzyme (17)(18)(19)(20). Because inhibitors of metalloenzymes typically contain a group that binds to the catalytic metal ion, we previously examined the cofactor preferences of MshB and found that MshB is a cambialistic metalloenzyme whose in vitro activity follows the following trend: Fe 2ϩ Ͼ Co 2ϩ Ͼ Zn 2ϩ Ͼ Mn 2ϩ Ͼ Ni 2ϩ (14).…”
Section: N-acetyl-1-d-myo-inosityl-2-amino-2-deoxy-␣-d-glucopyran-mentioning
confidence: 99%
“…MshB is an attractive drug target because it catalyzes the rate-limiting step in MSH biosynthesis (11), it is a metalloenzyme (12)(13)(14), and the three-dimensional structure is known (15,16). There are past successes in targeting metalloenzymes, including inhibitors of carbonic anhydrase, matrix metalloproteases, and angiotensin-converting enzyme (17)(18)(19)(20). Because inhibitors of metalloenzymes typically contain a group that binds to the catalytic metal ion, we previously examined the cofactor preferences of MshB and found that MshB is a cambialistic metalloenzyme whose in vitro activity follows the following trend: Fe 2ϩ Ͼ Co 2ϩ Ͼ Zn 2ϩ Ͼ Mn 2ϩ Ͼ Ni 2ϩ (14).…”
Section: N-acetyl-1-d-myo-inosityl-2-amino-2-deoxy-␣-d-glucopyran-mentioning
confidence: 99%
“…MshB is an attractive drug target because it is a metalloenzyme; there are past successes in targeting metalloenzymes, including inhibitors of carbonic anhydrase, matrix metalloproteases, and angiotensinconverting enzyme (12)(13)(14)(15). Inhibitors of metalloenzymes typically contain a group that binds to the catalytic metal ion.…”
Section: Enzyme Mshb Catalyzes the Hydrolysis Of N-acetyl-1-dmyo-inosmentioning
confidence: 99%
“…Further, inhibition of CAIX has been shown to result in regression or growth inhibition of mouse and human breast tumors as well as inhibition of cancer metastasis formation 25 . MMPs aid tumor progression by increasing cancer cell growth, migration and invasion, angiogenesis and metastasis 26,27 . In recent years, we have reported in a series of papers that show CPOs are able to act both in vitro and in vivo as inhibitors of the extracellular MMP 2 [16][17][18] and possess zinc-binding ability 28 .…”
Section: Discussionmentioning
confidence: 99%